Genome-Wide Identification of Apple Ubiquitin SINA E3 Ligase and Functional Characterization of MdSINA2 - Li, Hong-Liang; Wang, Xun; Ji, Xing-Long; Qiao, Zhi-Wen; You, Chun-Xiang; Hao, Yu-Jin (Frontiers in Plant Science, 2020)
SINA (Seven in absentia) proteins are a small family of ubiquitin ligases that play important roles in regulating plant growth and developmental processes as well as in responses to diverse types of biotic and abiotic stress. However, the characteristics of the apple SINA family have not been previously studied.Here, we identified 11 MdSINAs members in the apple genome based on their conserved, N‐terminal RING and C-terminal SINA domains. We also reconstructed a phylogeny of these genes; characterized their chromosomal location, structure and motifs; and identified two major groups of MdSINA genes. Subsequent qRT-PCR analyses were used to characterize the expression of MdSINA genes in various tissues and organs, and levels of expression were highest in leaves. MdSINAs were significantly induced under ABA and carbon- and nitrate-starvation treatment. Except for MdSINA1 and MdSINA7, the other MdSINA proteins could interact with each other. Moreover, MdSINA2 was found to be localized in the nucleus using Agrobacterium-mediated transient expression. Western-blot analysis showed that MdSINA2 accumulated extensively under light, decreased under darkness, and became insensitive to light when the RING domain was disrupted. Finally, ABA-hypersensitive phenotypes were confirmed by transgenic calli and the ectopic expression of MdSINA2 in Arabidopsis. In conclusion, our results suggest that MdSINA genes participate in the responses to different types of stress, and that MdSINA2 might act as a negative regulator in the ABA stress response.